Basic oral health knowledge and awareness among rural adults: A Cross-Sectional Study - Amanpreet Kaur Bhangu; Mehraab Dhillon; Karan Singh Ghuman; Mandeep Kumar; Richa Goel; Ramandeep Singh Gambhir (Wolters Kluwer Medknow Publications, 2021)
Background: It is very important to identify common oral health problems particularly in rural areas and create awareness for the same so that people can make informed choices. This study was conducted among the adult population residing in rural areas to assess their oral health knowledge and awareness. Materials and Methods: A descriptive cross-sectional study was conducted among adult population residing in rural areas around the dental clinic. A total of 662 participants constituted the final sample size after making necessary exclusions. A self-designed close-ended questionnaire written in English and Punjabi (local language) was constructed specifically for the study. The questionnaire was split into two sections. Analysis of variance and t-test were used in statistical analysis. Results: Majority of the participants (450, 68%) were male and 42.6% (282) of participants were in the age group of 41-50 years. Only 38% (251) of participants gave a positive response when asked about the importance of good oral health. About 40.2% (264) of participants believed that dental problems get cured solely by medicines. Low knowledge scores were recorded in 38.2% (252) of participants. Mean knowledge scores of the study participants were significantly associated with education (0.016) and occupation (0.027). Conclusion: Oral health knowledge and awareness among majority of study participants were not satisfactory. Therefore, the study emphasizes an urgent need for dental awareness and education programs targeting the rural masses.